2019
DOI: 10.1371/journal.pone.0218562
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and linkage disequilibrium using SNP (KASP) and AFLP markers in a worldwide durum wheat (Triticum turgidum L. var durum) collection

Abstract: The aim of this work was to analyze the genetic diversity and linkage disequilibrium in a collection of 168 durum wheat accessions (Triticum turgidum L. var. durum) of different origins. Our collection was mainly composed of released and unreleased Argentinian germplasm, with additional genotypes from Italy, Chile, France, CIMMYT, Cyprus, USA and WANA region. To this end, the entire collection was characterized with 85 Single Nucleotide Polymorphism (SNP) markers obtained by Kompetitive Allele Specific PCR (KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 69 publications
8
22
0
Order By: Relevance
“…In the GDP, the mean PIC values of 0.27 for landraces and 0.28 for modern lines and ranging from 0.09 to 0.38 (Table 2B) indicated a generally higher or similar level of genetic diversity captured within the GDP compared to previously studied collections. Recent studies reported PIC values of 0.26 for durum modern germplasm ( Chao et al, 2017 ), 0.19 for a set of both landraces and modern lines ( Ren et al, 2012 ), and 0.18 in a collection of 168 durum wheat accessions of different origins ( Roncallo et al, 2019 ). Analogously, AMOVA on clusters within GDP based on geography and breeding program of origin showed that only 13% of the total genetic variance could be captured among groups, while most diversity remained among individuals within clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In the GDP, the mean PIC values of 0.27 for landraces and 0.28 for modern lines and ranging from 0.09 to 0.38 (Table 2B) indicated a generally higher or similar level of genetic diversity captured within the GDP compared to previously studied collections. Recent studies reported PIC values of 0.26 for durum modern germplasm ( Chao et al, 2017 ), 0.19 for a set of both landraces and modern lines ( Ren et al, 2012 ), and 0.18 in a collection of 168 durum wheat accessions of different origins ( Roncallo et al, 2019 ). Analogously, AMOVA on clusters within GDP based on geography and breeding program of origin showed that only 13% of the total genetic variance could be captured among groups, while most diversity remained among individuals within clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, AMOVA on clusters within GDP based on geography and breeding program of origin showed that only 13% of the total genetic variance could be captured among groups, while most diversity remained among individuals within clusters. These results concur with those reported by Soriano et al (2016) with 172 landraces from 21 countries, by Roncallo et al (2019) with a panel of 168 durum accessions and by N'Diaye et al (2018) with a panel of Canadian durum cultivars where only 10% of variation was captured among groups. Other studies considering similar panels reported capturing over 30% of the total genetic variance by clustering germplasm based on kinship matrix, but using relatively higher k values (Kabbaj et al, 2017;Robbana et al, 2019).…”
Section: Genetic Diversity and Population Structure In Gdp And Breedisupporting
confidence: 90%
“…It is therefore evident that the passport information alone, while of great historical interest, is unable to capture the true genetic diversity of durum wheat worldwide. AMOVA on stratified groups may reveal much more variance among sub-populations, as indeed reported by other authors (Kabbaj et al, 2017;Roncallo et al, 2019). The moderate diversification among breeding groups (11.67% of the total variance) and very little among decades of release (2.95% of the total variance) revealed by AMOVA on the 473 modern durum wheat accessions (Tables 2D,E) was probably due to the wide and frequent exchange of parents among durum breeders worldwide.…”
Section: Genetic Diversity and Population Structure In Gdp And Breedisupporting
confidence: 82%
See 1 more Smart Citation
“…Molecular markers have been used very frequently in ecological, taxonomical, diversity, conservation, phylogenic and genetic studies amongst organisms (Avise 1994;Weising et al 2005;Sheth and Thaker 2017;Srivastava et al 2020). After the advent of Polymerase chain reaction (PCR) several advancements and introduction of new concepts were employed in the improvement of various types of molecular marker technologies like amplified fragment length polymorphism (AFLP) (Vos et al 1995;Roncallo et al 2019), inter simple sequence repeats (ISSRs), (Vanijajiva 2012;Husnudin et al 2019), random amplified polymorphic DNA (RAPD) (Vanijajiva et al 2005;Ihwan and Hakim 2019), Simple Sequence Repeats (SSR (Dewi et al 2020), Single Sequence Polymorphism (SNP) (Trick et al 2009;Luo et al 2010;Bayerl et al 2018). For distinct genetic applications amongst diverse plant species, different markers have been used by various researchers in commercial fruit accessions.…”
Section: Introductionmentioning
confidence: 99%